José Antonio Nieto (ed.), Antropología de la sexualidad y diversidad cultural. Talasa Ediciones, Madrid, 2003 - Castro Nogueira, Luis Alfonso (Empiria. Revista de metodología de ciencias sociales, 2004)
-